Impact of Technology-Based Clinical Documentation Improvement Program - Medical Coder Perspective - Harinath Babu, Jaibalaji (Digital Repository of Theses, 2026)
The rising use of tech-based clinical documentation improvement programs has changed how healthcare coding works, but not much research has looked at their effects from the point of view of medical coders. This study looks at how technology-enabled CDI platforms affect documentation quality, coding accuracy, workflow efficiency, and adoption behavior in outpatient healthcare settings. Grounded in the Technology Acceptance Model and Diffusion of Innovation theory, the research explores the relationships among perceived usefulness, ease of use, organizational support, and behavioral intention and how these factors contribute to measurable coding and documentation outcomes. A quantitative cross-sectional design was used based on data collected through a structured questionnaire administered to 372 medical coding professionals working in physician practices and outpatient environments. The instrument included validated TAM and DOI constructs adapted to the CDI context. Data was analyzed using descriptive statistics, reliability testing, exploratory factor analysis, correlation, and multiple regression techniques. Reliability and validity assessments confirmed the robustness of the measurement model. Results show strong positive perceptions of technology-based CDI programs across all major constructs. Perceived usefulness was found to be the strongest predictor for documentation quality and coding accuracy while ease of use had a significant influence on workflow efficiency. Organizational support in terms of training and managerial backing plays an important role in sustaining adoption as well as improving performance outcomes. Regression analysis results indicated that CDI technology significantly enhances identification of gaps in documentation and reduces operational inefficiencies. Correlation results further confirmed strong relationships among technology acceptance variables which support the theoretical framework. Most respondents were early-career coders who had limited exposure to CDI technology but reported real improvements in workflow and documentation processes, meaning that well-designed CDI platforms can give quick benefits even during early adoption stages. Diffusion of Innovation attributes overlapped with TAM constructs but were treated as contextual antecedents reinforcing their indirect influence on perceived usefulness and ease of use. The research ends with the idea that CDI programs using technology can improve coding and documentation practices if there are a strong organizational system and user-friendly ways to put them into action. These results offer real proof that CDI technology makes work easier for professionals and helps keep healthcare data correct. Practical results suggest focusing on training, ease of use, and fitting into current work processes to increase acceptance. Future studies should look at long-term effects and use real performance measures to confirm these results more thoroughly.